Spiderman is Not for Babies (Peter, 4 years): The “Boys and Reading Problem” from the Perspective of the Boys Themselves - McKechnie, Lynne E.F. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
Interviews were conducted with 43 Canadian boys, ages 4 to 12 years. The boys’ personal collections of reading and information materials were inventoried. Results indicate that boys are reading but their preferred reading materials (e.g., non-fiction, comic books, game manuals) are not those usually privileged by teachers, librarians and parents. Des entrevues ont été menées auprès de 43 garçons canadiens, âgés de 4 à 12 ans. Les collections personnelles de matériel de lecture et d’information ont été inventoriées. Les résultats indiquent que les garçons lisent, mais aussi que le matériel de lecture qu’ils préfèrent (i.e. non-fiction bandes dessinées, manuels de jeux) ne correspond pas au matériel habituellement privilégié par les professeurs, les bibliothécaires et les parents.